Leibniz: ¿hacia una nueva teoría de la sensibilidad? - Cubells Bartolomé, Maria Ramon (Revista de Filosofía de la Universidad de Costa Rica, 2014)
<span style="color: #000000; font-family: ’Times New Roman’; font-size: medium; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">The aim of this paper is to examine Leibniz’ theory of knowledge in terms of its relationship to the aesthetic universe inau- gurated by Baumgarten. Alexander Gottlieb Baumgarten (1714-1762) is well known for having used the concept of Aesthetica as the name of a new and independent discipline focusing on a “special” type of knowledge (concerning with sensitivity), that is characteristic of art and artistic beauty. Baumgarten was trained in the Wolffian school, but he had to return to the works of Leibniz to find an epistemology that would serve as the basis for an approach to sensible knowledge science, that could become a philosophical knowledge.